DEVELOPMENT PARTICIPATION AMONG ORANG ASLI IN SUNGAI BERUA VILLAGE, MALAYSIA - Abdullah, Ramle; Simin, Mohamad Hafis Amat; Ibrahim, Mohamad Asmawi (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2015)
The Orang Asli is one of the natives in Peninsular Malaysia lagging behind in rapid development, and has a high poverty rate. Although since the independence, Malaysian government has been implementing various development programs to solve the poverty problem, but the effect is not comprehensive. There are still tribes of Orang Asli less to participate in implementation of development programs. Instead, they are more focused on performing traditional economic activities especially hunting and gathering activities. Orang Asli from Semaq Beri tribes in the state ofTerengganu are among the communities that are in the situation. Based on this problem a study was made with the objective; (i) evaluate the implementation of development programs such as agriculture and fisheries projects that have been implemented for the locals, (ii) understand the problems faced by residents in their programs. To meet this objective, data were collected through observation techniques and interview process. Observation technique used to find out peoples reactions to the implementation of development programs, and interview techniques used to obtain information in the form of views and comments on the residents of the development. Studies of the documents were also made to get a clearer picture of the problem. The results showed that the implementation of development programs such as palm oil and fish farming cages less involving locals since the beginning of its implementation. Residents do not have sufficient information and skills to participate in this project. In addition, people also have trouble participating in the project on a number of factors such as lack of exposure, skills training, lack of guidance, leadership problems, culture and current financial problems